The Quality: Evolution of its meaning and application in service (Publicaciones en Ciencias y Tecnología, 2010)
The definition of quality has evolved over the last eighty years by the contributions of various authors and international organizations recognized by the scientific community. This article presents a documentary investigation of the chronological evolution of the definition of quality through the contributions of major philosophers or “gurus” of quality as well as international organizations who have contributed significantly to its suitability, study and dissemination. These definitions are applied and compared with some theories of quality of services, which include aspects such as its multidimensional nature, correspondence with attributes that meet customer needs and linked to customer satisfaction. You can see the validity of the theoretical tenets of the philosophers of quality, tested in a new form of society based primarily on services and information.
Keywords: Quality; philosophers of quality; service quality; information services; trends in services